Mesin Penyangrai Magot Untuk Komunitas Marginal Difabel Di Kelurahan Guwosari, Bantul, DI Yogyakarta - Hadi Saputra; Anak Agung Putu Susastriawan; Bambang Wahyu Sidartha; Jodi Purnomo Prasetyo (Fakultas Sains Terapan, 2024)
The Marginal Community with disabilities who are under the auspices of the Mekar Jaya organization in Guwosari village have a magot business unit. This effort has the potential to be able to prosper its members. The problem that exists for the process of making pellets for catfish feed is that it requires a magot drying process. Previously, this process was carried out traditionally with an ordinary fryer, the impact was low efficiency and productivity, the production capacity was only 50 kg/day. The solution to this problem is that we, from mechanical engineering, design and manufacture roasting machines to increase production. The productivity of this unit after using the roaster that we have disseminated increases to 100kg/day. The selling price of this magot is approximately Rp. 10,000.00 per kg so the estimated income from this magot per day will be Rp. 1.000.000.00. The community members feel grateful for the dissemination of this roasting